Enhancements to an indoor air flow device - Lo, Ai Jin (2014)
Mechanical ventilation is the primary mechanism for maintaining indoor air quality for modern buildings. Although each of them has their pros and cons, many studies have been performed to further improve their current capabilities. In the interest of predicting a customized airflow from a circulating fan, an external guiding vane was design and developed to achieve a direct-able airflow with the fan oscillating. Moreover, existing cooling methods were also explored to improve the cooling rate from the fan. Hypotheses were gathered by conducting preliminary experiment on a self-designed test rig using a stationary fan to direct airflow by a rectangular block. Additional experiments were conducted on the manufactured guiding vane prototype to verify its effectiveness. The formula derived from the results was able to achieve an accuracy of 78% for airflow estimation. The directed airflow velocity profile distributions were overall higher than the ones in normal oscillation. For the cooling aspect, the combination of using cooling pad and the prototype resulted in the greatest temperature drop observed. The idea of cooling pad may be a future solution to a cheaper yet effective alternative for better cooling applications. The findings shows that the prototype was deemed to be effective when the ambient temperature is above 28°C, average ambient airflow to be below 0.3m/s and average air humidity more than 50%. The use of the prototype together with the model created enables customized local airflow to be realized and predictable.